2014
DOI: 10.1007/s00267-014-0236-8
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Awareness and Public Support for Protecting and Restoring Puget Sound

Abstract: In an effort to garner consensus around environmental programs, practitioners have attempted to increase awareness about environmental threats and demonstrate the need for action. Nonetheless, how beliefs about the scope and severity of different types of environmental concerns shape support for management interventions are less clear. Using data from a telephone survey of residents of the Puget Sound region of Washington, we investigate how perceptions of the severity of different coastal environmental proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…Significant social factors leading to a positive attitude toward burning included landowners' previous experience, necessary skills and knowledge, risk taking orientation, and subjective norms. Finally, Safford et al (2014) found that awareness, attitude, and socio-demographic variables helped to predict support for resource protection and restoration efforts for Puget Sound in Washington State.…”
Section: Factors Affecting Supportmentioning
confidence: 99%
“…Significant social factors leading to a positive attitude toward burning included landowners' previous experience, necessary skills and knowledge, risk taking orientation, and subjective norms. Finally, Safford et al (2014) found that awareness, attitude, and socio-demographic variables helped to predict support for resource protection and restoration efforts for Puget Sound in Washington State.…”
Section: Factors Affecting Supportmentioning
confidence: 99%
“…In the individual dimension, that term refers to individual experiences and the way of thinking about nature, whereas in the collective dimension it refers to the standards of perception, experience, and evaluation of the biosphere. Some authors [22][23][24][25] indicate that environmental awareness is enhanced…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Today, Puget Sound is also home to 19 Native American tribes, the Southern Coast Salish, and their culture and communities are tightly linked to the Sound (Thrush 2009). The waters and shorelines of Puget Sound make up a unique estuarine system that is valued for its beauty and ecological importance (Safford et al 2014). Nonetheless, like other marine and estuarine ecosystems, Puget Sound has been affected by a variety of human activities, including agriculture, heavy industry, timber harvest, fishing, and the development of sea ports and residential property.…”
Section: Developing Social-ecological Targets: a Puget Sound-inspiredmentioning
confidence: 99%
“…Economists, for example, have methods for estimating values of ecosystem components that cannot readily be bought or sold (e.g., Carson et al 2001). Social scientists have used quantitative analysis of communication content (Neuendorf 2002), systematic surveys (Safford et al 2014), and workshops and individual interviews (Donatuto et al 2014) to evaluate preferences. Regardless of approach, the critical aspect of this step is that desirability is assessed for the complete suite of components of the socialecological system.…”
Section: Assess Ecosystem Preferencesmentioning
confidence: 99%
See 1 more Smart Citation